Assessing the Disposal Methods for End-of-Life Fishing Gears in Coastal Communities in Nigeria and its Implications on the Blue Economy - Abraham Ogheneruemu Ekperusi; Goodluck Marcus; Precious Kele (One Ocean Science Congress, 2025)
This study investigated the end-of-life fishing gear disposal methods in coastal communities and the implications on the blue economy in the Gulf of Guinea. We adopted questionnaires and focus group discussions for data collection among artisanal fishers. Females dominated the group compared to males, with most fishers within the age bracket of 41-50 years. Over one-third of the fishers had secondary education. The common disposal practices for damaged and end-of-life fishing gear include indiscriminate disposal in the terrestrial and aquatic environment, as well as burning and repurposing for domestic uses. Most fishers (92%) are unaware of the environmental consequences of improper gear disposal, indicating a severe lack of environmental education and the ecological implications of improper fishing gear disposal. Fishing gear destruction (90%), loss (60%) and gear entanglement are prevalent among fishers. Factors responsible for gear destruction and loss include barge operations (54.8%), strong tides (29%), large vessels (9.7%) and speedboats (7.5%). The main items entangling fishing gear include plastic bags, clothes, ghost gear and wood. Preventive measures undertaken by fishers include river lights and the attachment of coloured floaters as a signal to barges, vessels, and speedboats. Additional efforts include the use of strong ropes to avoid the cutting of nets. The study recommends implementing sustainable solutions, such as establishing gear recycling programmes, promoting biodegradable materials, and introducing reforms to incentivize fishers towards proper disposal practices for end-of-life fishing gears. Furthermore, education and community outreach are essential to increasing awareness and engagement in sustainable waste management.
Keywords: End-of-life fishing gear; Marine pollution; Marine debris; Gulf of Guinea; Ghost gear; Plastic pollution